Fiberoptic Bronchoscopic Balloon Dilatation of Bronchial Stenosis in Children. Issue 4 (October 2019) - Köse, Mehmet; Hangül, Melih; Erkan, Gözde Nur; Narin, Nazmi
Abstract : Background: Bronchial stenosis and treatment with balloon dilatation are rarely experienced in children. The aim of this study was to investigate the results of fiberoptic bronchoscopic balloon dilatation (BBD) in children. Methods: Between January 2016 and March 2018, 7 children diagnosed as having bronchial stenosis and who underwent BBD as the first treatment option were enrolled in the study. Results: A total of 10 BBDs were performed in 7 patients with a median age of 10 months. Underlying causes were as follows: prolonged intubation and prematurity in 4 patients, extubation failure in 2 patients, and recurrent pneumonia and malignancy in 1 patient. The only complication was laceration, seen in 2 patients. The patients were symptom free for 11 months. Conclusion: BBD is safe, effective, and might be the first-line treatment option for children with bronchial stenosis.